Freedom or Suffering: Post-Partition Memories and Fractured Identity Reflections in Jhumpa Lahiri’s Select Short-Fictions - Mandal, Sudeshna (Green University Review of Social Sciences, 2022)
The liberation of India from British domination in 1947 was the most significant historical event in the South Asian history. Despite the fact that freedom promised only liberty, equality, and fraternity, the only result was widespread violence, which eventually led to British-India being divided into two sovereign dominions (India and Pakistan). This Partition resulted in the loss of houses, properties, friends, relatives, and, most importantly, identity. The purpose of this paper is to look at how Jhumpa Lahiri addresses diasporic concerns, unpleasant partition experiences, and fractured cultural identity in two of her short- stories, “When Mr. Pirzada Came to Dine” and “A Real Durwan”, from her collection, Interpreter of Maladies. Lahiri, an Indian immigrant from the United Kingdom, is well aware of the difficulties that immigrants experience in their host country. She has brilliantly depicted the painful consequences of partition in the works described above, especially the bloodshed that occurs during the civil war between East and West Pakistan. The goal of this article is to examine how Lahiri uses these two short stories to emphasize the deceiving features of freedom. Green University Review of Social Sciences Dec 2021; 7(1-2): 105-111